Fluid Overload and Renal Angina Index at Admission Are Associated With Worse Outcomes in Critically Ill Children - Sethi, Sidharth K.; Raghunathan, Veena; Shah, Shilpi; Dhaliwal, Maninder; Jha, Pranaw; Kumar, Maneesh; Paluri, Sravanthi; Bansal, Shyam; Mhanna, Maroun J.; Raina, Rupesh (Frontiers in Pediatrics, 2018)
Objectives: We investigated the association of fluid overload and oxygenation in critically sick children, and their correlation with various outcomes (duration of ventilation, ICU stay and mortality). We also assessed whether renal angina index (RAI) at admission can predict mortality or acute kidney injury (AKI) on day 3 after admission. Design and setting: Prospective study, pediatric intensive care in a tertiary hospital Duration: June 2013- June 2014. Patients: Patients were included if they needed invasive mechanical ventilation for >24 hr and had an indwelling arterial catheter. Patients with congenital heart disease or those who received renal replacement therapy were excluded. Methods: Oxygenation index, fluid overload percent (daily, cumulative), RAI at admission and pediatric logistic organ dysfunction (PELOD) score were obtained in all critically ill children. KDIGO classification was used to define AKI, using both creatinine and urine output criteria. Admission data for determination of RAI included the use of vasopressors, invasive mechanical ventilation, percent fluid overload, and change in kidney function (estimated creatinine clearance). Univariable and multivariable approaches were used to assess the relations between fluid overload, oxygenation index and clinical outcomes. An RAI cutoff >8 was used to predict AKI on day 3 of admission and mortality. Results: One hundred and two patients were recruited. Fluid overload predicted oxygenation index in all patients, independent of age, gender and PELOD score (p <0.05). Fluid overload was associated with longer duration of ventilation (p <0.05), controlled for age, gender, and PELOD score. Day-3 AKI rates were higher in patients with a RAI of 8 or more, and higher areas under the RAI curve had better prediction rates for Day-3 AKI. An RAI <8 had high negative predictive values (80-95%) for Day-3 AKI. RAI was better than traditional markers of pediatric severity of illness (PELOD) score for prediction of AKI on day 3. Conclusions: This study emphasizes that positive fluid balance adversely affects intensive care in critically ill children. Further, the renal angina index prediction model may help optimize treatment and improve clinical prediction of AKI.